42 Thromboprophylaxis in the last days of life. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Martin, Alice; Valentine, Emma
Abstract : Background: Venous thromboembolism (VTE) is a well-established cause of in-hospital mortality. Consequently, prevention is a vital part of patient care. Nevertheless, in patients approaching the end of life, VTE prophylaxis should be reviewed daily, with decision-making taking into account the views of the patient and carers. NICE advises VTE prophylaxis should not be offered to people in their last days of life. Methods: We undertook a retrospective review of the case-notes of all patients who died at a district general hospital in the month 17th September – 17th October 2018. We aimed to assess whether patients dying in the acute hospital were: Commenced on VTE prophylaxis during admission; Recognised as dying; Commenced on the hospital's individualised care plan for the last days of life; Receiving VTE prophylaxis in the 72 hours before death. Results: 96 patients died within the review period. 5 deaths in the emergency department were excluded. Of the remaining 91, the median age was 82. 47 out of the 91 patients (52%) received VTE prophylaxis during their hospital admission. 68 patients (75%) were recognised as dying, and of these, 40 (59%) were commenced on the hospital's individualised care plan for the last days of life. 25 patients received VTE prophylaxis within the last 72 hours of life. Of these, 12 had VTE prophylaxis stopped in the coming days. 6 patients who were recognised as dying received VTE prophylaxis in their last 24 hours of life. Conclusions: The results suggest that guidance regarding pharmacological thromboprophylaxis in the last days of life is not consistently followed even when the dying process has been recognised. They also highlight that improvement is needed in recognising the dying patient in the acute setting and that locally there is inadequate uptake of our 'last days of life' care plan.